Novel P-n Li2SnO3/g-C3N4 Heterojunction With Enhanced Visible Light Photocatalytic Efficiency Toward Rhodamine B Degradation - Li, Yuanyuan; Wu, Meijun; Wang, Yaoqiong; Yang, Qimei; Li, Xiaoyan; Zhang, Bin; Yang, Dingfeng (Frontiers in Chemistry, 2020)
The design of highly efficient and stable photocatalysts to utilize solar energy is a significant challenge in photocatalysis. In this work, a series of novel p-n heterojunction photocatalysts, Li2SnO3/g-C3N4, was successfully prepared via a facile calcining method, and exhibited superior photocatalytic activity toward the photodegradation of Rhodamine B solution under visible light irradiation as compared with pure Li2SnO3 and g-C3N4. The maximum kinetic rate constant of photocatalytic degradation of Rhodamine B within 60 min was 0.0302 min-1, and the composites still retained excellent performance after four successive recycles. Chemical reactive species trapping experiments and electron paramagnetic resonance demonstrated that hydroxyl radicals (∙OH) and superoxide ions (∙O_2^-) were the dominant active species in the photocatalytic oxidation of Rhodamine B solution, while holes (h^+) only played a minor role. We demonstrated that the enhancement of the photocatalytic activity could be assigned to the formation of a p-n junction photocatalytic system, which benefitted the efficient separation of photogenerated carriers. This study provides a visible light-responsive heterojunction photocatalyst with potential applications in environmental remediation.